LUMINESCENCE STUDIES ON INTRAZEOLITIC MIGRATION OF TB(III) IONS BY THERMAL TREATMENTS .1. FAU-TYPE ZEOLITES - HONG, SB; SHIN, EW; MOON, SH; PYUN, CH; KIM, CH; UH, YS (AMER CHEMICAL SOC, 1995)
It is observed from the luminescence measurements that the intrazeolitic migration of Tb(III) ions arising from thermal treatments in FAU-type zeolites is strongly dependent on the framework Si/Al ratio. For a low-silica FAU zeolite (Si/Al = 1.37) most of the Tb(III) ions exchanged into supercages begin to migrate directly to hexagonal prisms at 423 K without staying at sodalite cages; by contrast, the cations in a high-silica FAU zeolite (Si/Al = 3.40) migrate first to sodalite cages at 373 K and in turn to hexagonal prisms at temperatures higher than 373 K.
Keywords: EXCHANGED Y-ZEOLITES; RARE-EARTH; CATION DISTRIBUTION; NMR; FRAMEWORK; SPECTRA; METAL